Translational medicine and drug discovery - Littman, Bruce H. 1944-; Krishna, Rajesh (Cambridge University Press, 2011)
"Focuses on the new discipline of translational medicine as it pertains to drug development within the pharmaceutical and biotechnology industry"--Provided by publisher.